PPARA and IL6: Exploring associations with athletic performance and genotype polymorphism - ULUCAN, KORKUT (My University, 2023)
This study aims to investigate the Interleukin (IL)-6 rs1800795 and peroxisome proliferator-activated receptor alpha (PPARA) rs4253778 polymorphism distributions in the relatively faster and slower subgroups of national cross-country skiing athletes and to identify advantageous genotypes for endurance performance. IL-6 is an inflammatory mediator that is effective in muscle tissue hypertrophy, repair, and the immune system. On the other hand, PPARA transcription factor is a molecule associated with fatty acid, sugar metabolism and inflammation formation. Total of 30 professional cross-country skiing athletes were examined in three groups as athletes, female athletes, and male athletes. DNA of the participants were isolated from blood and genetic polymorphisms were determined by RT-PCR. Athletes were divided into two subgroups as faster and slower referring to their “1-kilometer cross-country skiing time averages (CCSTA)”. Polymorphism distributions in these subgroups were analyzed statistically with Fisher's exact test and descriptive tests. In addition, the 1 kmCCSTA values of the genotypes were determined by descriptive statistical methods and the time advantages were calculated. It was determined that the combination of IL-6 rs1800795 GC and PPARA rs4253778 GG genotypes was observed to be more prominent among the faster categories of cross-country skiing competitors, particularly in the athletes and male athletes categories, and it had a time advantage at 1 km-CCSTA. The GC genotype (p= 0.0098) and C-allele (p=0.0398) of IL-6 rs1800795 polymorphism were detected at a higher rate in the fast subgroup in male athletes. These genotypes may support endurance performance.
Keywords: IL-6; PPARA; cross-country skiing athletes; Athletic performance; Sports genetics